Some International Issues in Commodity Taxation - Keen, Michael (Washington, D.C. : International Monetary Fund, 2002)
This paper reviews issues and evidence concerning tax-motivated, cross-border commodity transactions. A distinction is drawn between "arbitrage trades" (driven by cross-country differences in tax rates) and "tax not paid" transactions (motivated by the opportunity to pay no tax at all on transactions with international aspects). Assessment of the severity of the associated policy problems faces the difficulty that the observed extent of cross-border transactions conveys no information on the induced inefficiency that the possibility of such transactions may generate. Given the difficulty of securing coordination of national tax policies, much of the emphasis in dealing with these problems in the coming years is likely to be on administrative cooperation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet